Success Model of Learning by e-Learning in Higher Education - Wagimin, Ign.; Ninghardjanti, Patni; Kritistiani, Kristiani (Universitas Negeri Makassar, 2014)
The research aims to 1) identify and describe the level of use of e-learning system by students and faculty and 2) identify the factors that influence the success of e-learning in higher education. The study was conducted at the UNS and UMS with 160 respondents. The sampling technique with cluster sampling followed by accidental sampling. Model tested for stalling the success of e-learning is a model DeLone and McLean. Estimation techniques used are generalized Least Square Estimation and analysis of the relationship between variables is done with SEM. This study found that more women are using elearning as compared with men, successful implementation of e-learning in college is strongly influenced by the perception of user satisfaction and perception of the use of elearning systems